2022
DOI: 10.20473/mgi.v17i2.204-212
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Choices of Healthy Diet among Adolescents in Rural Areas

Abstract: Many adolescents tend to pick unhealthy diets with high amount of sugar, salt and fat, while the number of adolescents who consume vegetables and fruit is relatively low. As adolescents begin to pick their own diets by themselves, there are certain reasons behind each of their preferences in foods. This study was aimed to analyze the factors affecting the choices of healthy diet among adolescents in rural areas. This was quantitative research with analytical and observational research method with a cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
1
0
0
1
Order By: Relevance
“…In line with the different results of previous studies on portion size influenced by social and psychological contexts, we also found that most studies on eating behaviour apply behavioural measurements in experimental settings (such as in the US, UK, and the Netherlands) using behavioural measurement, lab-based experiments, observations, and online experiments (Baker et al, 2019;Hermans et al, 2012;Otterbring, 2018;Robinson et al, 2022;Ruddock, Long, et al, 2021). However, in Indonesia, there has been a heavy reliance on subjective measurements, including self-reporting, surveys and FGD (Dewanti et al, 2022;Habibie et al, 2019;Risti et al, 2021), yet few studies have used behavioural measurements of food choices and portions. Indeed, behavioural measurement studies provide observable data without requiring participants to report their inner states.…”
Section: Introductionsupporting
confidence: 86%
“…In line with the different results of previous studies on portion size influenced by social and psychological contexts, we also found that most studies on eating behaviour apply behavioural measurements in experimental settings (such as in the US, UK, and the Netherlands) using behavioural measurement, lab-based experiments, observations, and online experiments (Baker et al, 2019;Hermans et al, 2012;Otterbring, 2018;Robinson et al, 2022;Ruddock, Long, et al, 2021). However, in Indonesia, there has been a heavy reliance on subjective measurements, including self-reporting, surveys and FGD (Dewanti et al, 2022;Habibie et al, 2019;Risti et al, 2021), yet few studies have used behavioural measurements of food choices and portions. Indeed, behavioural measurement studies provide observable data without requiring participants to report their inner states.…”
Section: Introductionsupporting
confidence: 86%
“…99% remaja makan siang setiap hari di rumah makan bersama teman-temannya. Selain itu pemilihan makan juga dapat dipengaruhi oleh beberapa faktor yaitu kepedulian terhadap kesehatan, keakraban (familiaritas makanan), daya tarik sensorik, suasana hati, kenyamanan, harga, pengendalian berat badan, kandungan alami dan masalah etika, dari kesembilan faktor tersebut terdapat tiga alasan utama dalam pemilihan makanan pada remaja yaitu kesehatan, kandungan alami, dan pengendalian berat badan, didukung dengan hasil uji statistik yang menunjukan bahwa terdapat hubungan antara faktor kepedulian terhadap kesehatan, pengendalian BB dan kandungan alami terhadap pemilihan makanan sehat pada remaja di pedesaan (p=< 0,005) (Dewanti et al, 2022).…”
Section: Pembahasanunclassified